2018
DOI: 10.1101/492645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of a cytochrome-based bacterial nanowire

Abstract: Electrically conductive pili from Geobacter species, termed bacterial "nanowires", are intensely studied for their biological significance and potential in the development of new materials. We have characterized a unique nanowire from conductive G. sulfurreducens pili preparations by cryo-electron microscopy composed solely of the c-type cytochrome OmcS. We present here, at 3.4 Å resolution, a novel structure of a cytochrome-based filament and discuss its possible role in long-range biological electron transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Immunogold labeling has demonstrated that both OmcS (26, 31) and OmcZ (32) can associate with the outer cell surface and thus are properly localized to function as electrical contacts between cells and Fe(0). Under some conditions, OmcS may also extend at distance from the cell, either attached to pili (26, 33, 34) or as filaments composed of OmcS (35). However, filament extensions are unlikely to be important for electron transfer from Fe(0) because the cells are in close contact with the Fe(0) surface.…”
Section: Resultsmentioning
confidence: 99%
“…Immunogold labeling has demonstrated that both OmcS (26, 31) and OmcZ (32) can associate with the outer cell surface and thus are properly localized to function as electrical contacts between cells and Fe(0). Under some conditions, OmcS may also extend at distance from the cell, either attached to pili (26, 33, 34) or as filaments composed of OmcS (35). However, filament extensions are unlikely to be important for electron transfer from Fe(0) because the cells are in close contact with the Fe(0) surface.…”
Section: Resultsmentioning
confidence: 99%
“…[14,30] A recent report showed that G. sulfurreducens conductive filaments were assembled by hexaheme cytochrome OmcS, with a tight packing distance at 3.5-6 Å over a micrometer length, [31] corroborated by interatomic distances between adjacent porphyrins of the hexaheme cytochrome at 4.1 Å or less. [32] Moreover, the polymerization of monomeric cytochromes (e. g. OmcZ) could further reduce the heme-heme distance. [33] At such closely packed distance, multistep electron hopping along the conductive filaments thus are made possible (< 20 Å).…”
Section: Introductionmentioning
confidence: 99%
“…Dcyt m 2 s -1 10 -5 -10 -10 (7×10 -7 ) Effective diffusion coefficient Estimated from [116][117][118] kD m 4 mol s -1 10 -5 -10 5 (100) Electron transfer rate constant Estimated from Dcyt = kD[Cyttot]δ δ nm 0.7 Spatial distance between adjacent redox-active molecules [119] σ S m -1 10 -4 -10 -2 (1.5×10 -3 ) Biofilm conductivity [12,21,35,120] Anw m 2 1.26×10 -17 Cross-section area of a single pilus Calculated from dnw dnw nm 4 Diameter of a single pilus [31,32] Aact m 2 10 -14 -10 -13 Redox active surface area Estimated from [108] β -0.5 Charge transfer coefficient [108] ϕanode V -0.1, +0.24 Poised low, high anode potential [58] ϕox/red 0' V -0.07, -0.15 Redox-active center mid-potential [44,56] Nnw,cell -1-200 (49) Number of connections per cell Estimated from [32,[108][109][110][111] Fixed concentration were imposed for all chemical species at the outer domain boundary except for CO2, CO3 2-, Cytred, R-COOH, R-NH2, R-PO4H2. No flux conditions were imposed at the bulk-biofilm interface and anode surface for CO2, CO3 2-, Cytred.…”
mentioning
confidence: 99%
“…[ 152 ] The recent discovery using cryo‐electron microscopy showed that some pili from conductive G. sulfurreducens contain in the center of the filament a chain of head‐to‐tail stacked outer membrane OmcS, leading to a nanowire that is apparently also involved in long‐range electron transfer. [ 153 ]…”
Section: Mechanisms Of Microbial Synthesis Of Nanoparticlesmentioning
confidence: 99%